MENGUATKAN BRANDING TENUN ENDEK KHAS BULELENG MELALUI REVITALISASI PEWARNAAN DENGAN FIKSATOR NANOPASTA ANORGANIK BERBAHAN ABU VULKANIK GUNUNG AGUNG - Karyasa, I Wayan; Astawa, I Gede Putu Banu; Pradnyana, I Gede Ardwi; Oviantari, Made Vivi (Universitas Pendidikan Ganesha, 2021)
In the Covid-19 pandemic era, most of craft industries, including Buleleng endek ethnical woven crafts, had an impact on sales drastically. Woven craft industries did some preventive efforts, one of them was through enhancing ecofriendly industry branding, i.e. through intensifying yarn dying using natural colors from local raw materials. However, the main problems on color quality, color fastness, tensile strength and ductile ability of colored yarns resulted by natural dyeing should be handled. Our current finding on inorganic nanopaste fixator of natural colors could be as solution. The natural color dyeing technology was applied for cotton as well as silk yarn by using local color natural resources. It resulted that the yarns had better color quality, good grade color fastness and higher tensile strength and ductile ability. The industrial partner had good response on the natural dyeing technology, where it was also supported by good response from costumer candidates of the endek woven crafts. The revitalization of natural dyeing technology through applying inorganic fixator nanopaste affected the stronger branding of Buleleng endek woven crafts through enhancing the selling revenue.